Human Neutrophil Defensins Disrupt Liver Interendothelial Junctions and Aggravate Sepsis - QiXing Chen; Yang Yang; YiHang Pan; LiHua Shen; Yan Zhang; Fei Zheng; Qiang Shu; XiangMing Fang (Mediators of Inflammation)
Human neutrophil peptides 1-3 (HNP1-3), also known as human α-defensins, are the most abundant neutrophil granule proteins. The genes that encode HNP1-3, DEFA1/DEFA3, exhibit extensive copy number variations, which correlate well with their protein levels. Human and mouse studies have shown that increased copy numbers of DEFA1/DEFA3 worsen sepsis outcomes. Additionally, high concentrations of HNP1-3 in body fluids have been reported in patients with sepsis. However, direct evidence for the pathogenic role of HNP1-3 proteins during sepsis progression is lacking. In current study, sepsis was induced by means of cecal puncture and ligation. Various doses of HNP-1 (low dose with 0.5 mg/kg body weight and high dose with 10 mg/kg body weight) or phosphate buffer saline were intraperitoneally administered to mice at six hours after sepsis onset. Survival rate was monitored, and vascular permeability, endothelial cell pyroptosis, and immunofluorescence of endothelial adherens junction protein vascular endothelial-cadherin were evaluated. The administration of a high dose of HNP-1 after sepsis onset led to increased mortality, more severe liver injury, and increased vascular permeability in the liver and mesentery. The injection of high dose of HNP-1 did not directly induce liver endothelial cell death but destroyed interendothelial junctions in the liver. Moreover, genetic deficiency of nucleotide-binding oligomerization domain-like receptor protein-3 or caspase-1 abrogated the high mortality and disrupted liver interendothelial junctions caused by high dose of HNP-1 during sepsis. This study directly demonstrates that neutrophil defensins play a key role in regulating endothelial stability during sepsis development.